2020
DOI: 10.31234/osf.io/pc4uh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human larynx motor cortices coordinate respiration for vocal-motor control

Abstract: Vocal flexibility is a hallmark of the human species, most particularly the capacity to speak and sing. This ability is supported in part by the evolution of a direct neural pathway linking the motor cortex to the brainstem nucleus that controls the larynx ¬– the primary sound source for communication. Early studies demonstrated that a larynx motor area at the dorsal end of the orofacial division of motor cortex (dLMC) integrated laryngeal and respiratory control, thereby coordinating two major muscular system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…We have independently suggested that dPM is part of the cortical circuit for laryngeal motor control (Hickok, 2017). Therefore, one hypothesis is that dPM responds to multiple aspects of speech motor control during production (Belyk et al, 2020;Cheung et al, 2016) but responds preferentially to pitch/voicing during perception (Cheung et al, 2016), which may owe to the presence of non-identical subpopulations of neurons coding auditory and motor features, respectively, as is typical of brain regions involved in sensorimotor integration (Sakata, Taira, Murata, & Mine, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We have independently suggested that dPM is part of the cortical circuit for laryngeal motor control (Hickok, 2017). Therefore, one hypothesis is that dPM responds to multiple aspects of speech motor control during production (Belyk et al, 2020;Cheung et al, 2016) but responds preferentially to pitch/voicing during perception (Cheung et al, 2016), which may owe to the presence of non-identical subpopulations of neurons coding auditory and motor features, respectively, as is typical of brain regions involved in sensorimotor integration (Sakata, Taira, Murata, & Mine, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Our vLMC seed co-ordinate was derived from the first dMRI study on stuttering ( x = −48, y = −15 and z = 18) ( Sommer et al , 2002 ). This white-matter site is closely located to sites of cortical activity reported for tasks that were designed to stimulate and differentiate dLMC and vLMC brain activity during whistling and singing ( x = −59, y = −16 and z = 13) ( Belyk et al ., 2020 ) or vocalization and vowel production ( x = −58, y = −2 and z = 20) ( Eichert et al ., 2020 ). Similarly, earlier fMRI studies that investigated vowel production ( Grabski et al , 2012 ), vocal imitation ( Belyk et al , 2016 ), pitch ( Peck et al , 2009 ), cough ( Mazzone et al , 2011 ) and brain alterations in spasmodic dysphonia ( Simonyan and Ludlow, 2012 ) relate laryngeal control to our chosen vLMC co-ordinate.…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, earlier fMRI studies that investigated vowel production ( Grabski et al , 2012 ), vocal imitation ( Belyk et al , 2016 ), pitch ( Peck et al , 2009 ), cough ( Mazzone et al , 2011 ) and brain alterations in spasmodic dysphonia ( Simonyan and Ludlow, 2012 ) relate laryngeal control to our chosen vLMC co-ordinate. Cyto- and myeloarchitecture of the ventral laryngeal representation is currently unknown and it has been suggested that this region might belong to the cytoarchitectonic area 6 ( Pfenning et al , 2014 ; Dichter et al , 2018 ; Jarvis, 2019 ; Eichert et al ., 2020 ) or to the cytoarchitectonic area 43 ( Belyk and Brown, 2017 ; Belyk et al ., 2020 ). Besides this dissent, different research groups seem to agree on the idea that the vLMC does not belong to the primary motor cortex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations